Застосування професійно-психологічного квесту у професійній підготовці поліцейських - Мілорадова, Н. Е.; Miloradovа, N. E.; ORCID: http://orcid.org/0000-0002-0716-9736; Твердохлєбова, Н. Є.; Tverdokhliebova, N. Ye.; ORCID: https://orcid.org/0000-0003-3139-4308 (Право і безпека. - 2021. - № 1 (80). - С. 109-116, 2021)
Презентовано результати аналізу зарубіжних і вітчизняних підходів до трактування, функцій та класифікації квест-технологій. Зазначено, що з метою створення належних умов для формування професійної компетентності майбутніх поліцейських, мотиваційної спрямованості на позитивні особистісні зміни та бажання професійного саморозгортання доцільно використовувати можливості інноваційних технологій навчання, зокрема тренінгів і квестів. Виокремлено освітній квест як окрему форму проєктних технологій. Розкрито особливості розробленого професійно-психологічного поліцейського квесту з елементами тренінгу «Особливості діяльності дільничного офіцера поліції (ДОП)», охарактеризовано його послідовні етапи: організаційно-підготовчий, реалізації та заключний.

The results of the analysis of foreign and domestic approaches to the interpretation and under standing of quest technologies are presented. It is noted that in order to create the proper con ditions for the formation of future police officers professional competence, motivational focus on positive personal changes and the desire for professional self-development, it is advisable to use the possibilities of innovative teaching technologies, in particular, trainings and quests. During such classes, participants have the opportunity to learn how to quickly make the right decisions within the limits of their professional competence, applying the obtained theoretical knowledge, as well as to master and consolidate the necessary skills. The educational quest is highlighted as a separate form of design technologies. The features of the developed profes sional-psychological police quest with elements of the training "Features of the district police officer’s activities" are revealed, its consistent stages are characterized: organizational and preparatory, implementation and final. It is noted that the basis of the police quest is the situa tional method, the content of which is aimed at mastering the algorithm of actions by the ca dets associated with the implementation of the service tasks of the police. It has been revealed that the use of a professional-psychological police quest is an active form of group work and provides the use of set measures aimed at increasing the level of professional training of police officers, developing and changing the structure of interpersonal relations, educational and pro fessional motivation, and contributes to the self-realization of the individual within the profes sional space. The authors emphasize the advisability of using a police quest, which contributes to the increase of professional competence level due to the increase of the study time amount allocated for practical work, the independent acquisition and use of new knowledge and skills in practice, making the right decisions within the framework of their professional competence, and well-coordinated teamwork.

Приведены результаты анализа зарубежных и отечественных подходов к трактовке, пониманию функций и классификации квест-технологий. Отмечено, что с целью создания надлежащих условий для формирования профессиональной компетентности будущих полицейских, мотивационной направленности на положительные личностные изменения и желание профессионального саморазвертывания целесообразно использовать возможности инновационных технологий обучения, в частности тренингов и квестов. Выделен образовательный квест как отдельная форма проектных технологий. Раскрыты особенности разработанного профессионально-психологического полицейского квеста с элементами тренинга «Особенности деятельности участкового офицера полиции (УОП)», охарактеризованы его последовательные этапы: организационноподготовительный, реализации и заключительный.
Применение профессионально-психологического квеста в профессиональной подготовке полицейских
Application of the professional psychological quest in the professional training of police officers
Мілорадова Н. Е. Застосування професійно-психологічного квесту у професійній підготовці поліцейських / Н. Е. Мілорадова, Н. Є. Твердохлєбова // Право і безпека. - 2021. - № 1 (80). - С. 109-116. - DOI: 10.32631/pb.2021.1.15.
Мілорадова, Н. Е. і Твердохлєбова, Н. Є. (2021) «Застосування професійно-психологічного квесту у професійній підготовці поліцейських», Право і безпека, 80(1), с. 109-116. doi: 10.32631/pb.2021.1.15.
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; квест-технології; освітній квест; професійно-психологічний квест; правоохоронці; дільничні офіцери поліції; квест-технологии; образовательный квест; профессионально-психологический квест; правоохранители; участковые офицеры полиции; quest technologies; educational quest; professional psychological quest; law enforcement officers; district police officers